1988
DOI: 10.1159/000461790
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transfusion Non-A, Non-B Hepatitis: Significance of Raised ALT and Anti-HBc in Blood Donors

Abstract: The FDA has recommended that all blood collected in the USA should be screened for antibody to hepatitis B core antigen (anti-HBc) and for raised alanine aminotransferase (ALT) as possible indicators of non-A, non-B hepatitis carriage. As part of an assessment of the medical and economic implications of such a screening programme, we have screened 1,742 regular blood donors for ALT and 2,086 (including the same 1,742) for anti-HBc. 42 (2.4%) of the 1,742 donors had ALT levels above 45 units/l. Clinical assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
2

Year Published

1989
1989
1993
1993

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
8
2
Order By: Relevance
“…Amongst the rest, about one quarter (6% of all donors) exhibited ALT elevation in consecutive dona tions, for an average 4.3 adjacent donations, but none ex hibited >100 IU/1 in consecutive donations. Our previous studies [14] would suggest that a non-virological cause will be found for the majority of these, as was shown in the recent UK multicentre study [6]. In contrast to our data the …”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Amongst the rest, about one quarter (6% of all donors) exhibited ALT elevation in consecutive dona tions, for an average 4.3 adjacent donations, but none ex hibited >100 IU/1 in consecutive donations. Our previous studies [14] would suggest that a non-virological cause will be found for the majority of these, as was shown in the recent UK multicentre study [6]. In contrast to our data the …”
Section: Resultscontrasting
confidence: 85%
“…If ALT elevation is an essentially random event, rather than occuring consistently in a few identifiable donors, it has been estimated that up to 50% of a donor panel might be lost over a 10-year-period for groups such as plasmaphere sis donors who give blood frequently [5]. The limited du ration studies that have been performed to date indicate persistent ALT elevation in 25-66%, and intermittent ele vation of 30-80% of such donors [4,5,14,29,30], Following a preliminary study at this Centre [14], the retrospective study described above was undertaken on ALT results in plasmapheresis donors over a period of 18 months. The results of this study show that, as expect ed, about 2.5% of donations had an ALT above the upper limit of normal.…”
Section: Resultsmentioning
confidence: 99%
“…It was found in this study that the markers ALT and anti-HBc are not usually associated and detect different donor populations, which had also been established by others [13,14,30,31]. Anti-HBc antibodies had no signif icant association with recipient NANBH risk, as in other recent studies [4,17,18] also performed after widespread exclusion of the human immunodeficiency virus risk groups from blood donation.…”
Section: Anti-hcvsupporting
confidence: 82%
“…As it is raised, the test becomes more specific but less sensitive. The prevalence of elevated ALT has clear geographic var iation and is significantly associated with gender, age and body weight [30][31][32][33]. We found slightly lower prevalences of raised ALT values among our donor population than reported from the USA, the UK and the Netherlands, 1.99% of our donor samples being at or above the log mean ALT + 2.0 SD as compared with 2.6 and 2.2% in the USA, approximately 3.6% in the UK and 3.8% in the Nether lands [1,26,29,34], The ALT exclusion level with maximal significance of association with recipient hepatitis was 2.0 SD above the log mean in our material, and +2.0 or +2.25 SD in the two American materials [1,34], A difference was found in this significance itself, the p value being only 0.02 in this study, <0.05 in that of van der Poel et al [29] but <0.001 and <0.00001 in the reports from the USA [1,34], This might mean that in Finland and the Netherlands there are relatively more nonviral reasons for elevated ALT.…”
Section: Anti-hcvmentioning
confidence: 99%
“…I am writing to you concerning a paper authored by Gillon et al [ 1 ] that was published recently in Vox San guinis. It is stated in this paper that 'The FDA has rec ommended that all blood collected in the USA should be screened for antibody to hepatitis B core antigen (antiHBc) and for raised alanine aminotransferase (ALT) as possible indicators of non-A, non-B hepatitis carriage' and further that 'the FDA last year issued a recommen dation that both tests should be carried out by all blood collecting agencies'.…”
mentioning
confidence: 99%